Polysaccharides Based Novel and Controlled Released Multiparticulate Systems for Colon-specific Delivery: Contemporary Scenario and Future Prospects - Lanjhiyana, Dr. S. K. (Asian Journal of Pharmaceutics (AJP), 2020)
In our noble pharmaceutical field, polysaccharides were become an indispensable part during dosage form development for the last few decades. The matrix polysaccharides that were utilizing for dosage form were mostly hydrophilic in nature that gets swell and form a viscous gel-like mass upon contact with dissolution fluids or gastrointestinal fluids. The polymeric properties were successfully exploited in the development of novel polyelectrolyte complexes based multiparticulate delivery systems based on ionic gelation techniques. These complex systems have awaken as an emerging need to deliver the drug(s) into the target site of action for possible controlling and sustaining the drug release properties and thereby affecting the pharmacological responses other than those traditional dosage forms. Site-specific deliveries to the colon were confirmed for providing enzymatic digestion of those polysaccharides. Furthermore, in the present review, an attempt was made to describe the significance of the physicochemical properties of those polysaccharides for defining its possible mechanism of actions.